'Muslim is the new black': new ethnicities and new essentialisms in the prison - Earle, Rod (2013)
Drawing from a recent qualitative study of identity, ethnicity, and social relations intwo English prisons, the authors reflect on Stuart Hall’s formulation of a new ethni-cities paradigm. Using a vignette case study and the comments of a range of prisoners,they consider how persistent patterns of racism are reproduced and challenged in theprison and beyond. British and penal historical and cultural contexts are provided tofacilitate an empirically informed discussion of plural and evolving racisms, new eth-nicities, and Islamophobia. An argument is presented that suggests a thinly theorizedunderstanding of ethnicity is assuming the status of a falsely benign orthodoxy, onethat shrouds the familiar and painful injuries of racism.